Islamic Entrepreneurship Character Education in the Digital Era: Strategy for Creating Sharia-Based Entrepreneurs - Najmudin, Najmudin; Ngulwiyah, Istinganatul; Aziz, Abdul (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2024)
Islamic entrepreneurial character education in the digital era is important along with the development of technology and the challenges faced by entrepreneurs in maintaining business ethics. This study aims to analyze Islamic character education strategies that can be applied in sharia-based entrepreneurship, especially in the digital world. With a literature study approach, this study examines the concept of Islamic entrepreneurship, values such as honesty, trustworthiness, blessings, responsibility, and justice, as well as the influence of technology on business practices. The research findings show that Islamic character education is very important in forming entrepreneurs who are not only competent, but also ethical, with a focus on Islamic values that are the basis for making business decisions. Although challenges such as global competition and rapid technological developments continue to grow, these values are an important foundation in facing these challenges. The use of digital technology, such as e-learning and sharia fintech, also has an important role in supporting the development of more efficient and inclusive Islamic entrepreneurship.